Um modelo para a avaliação da qualidade de dados em sistemas transacionais - SANTOS, Marcio Henrique Alves dos (2014)
Data quality can be a determining factor in the performance of an organization . The poor quality of data can negatively impact , making the decision -making processes are compromised. Quality problems can arise from many different sources , whether the software processing errors , failures in determining requirements or failures in the data load process in the systems . This paper presents a Model for Assessing the Quality of Data in Transactional systems from the perspective of the user. Its function is to facilitate the provision of information about the quality of data in transactional systems. Are presented on a tool, FEMEQ that uses triggers to assist in measuring the quality of data in an automated way and a process model for the assessment of data quality from the perspective of user. For the application of the proposed model based on process and FEMEQ a case study was conducted in three organizations that use software to different domains so that the quality of data in these systems could be inferred. This case study allowed us to identify the validity of the proposed model as well as benefits accrued by its use.